2022
DOI: 10.1016/j.scs.2022.103770
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of mobility on the incidence of COVID-19 in Dublin City

Abstract: Covid-19 has had a major impact on the transport systems around the world. Several transport-related policies were implemented in short period of time to contain the spread of the pandemic. These policies had a major influence on travel behaviour and people's perception towards the safety of different modes of transport, especially public transport, thus affecting several sustainable mobility initiatives. To build a resilient and sustainable transport system and to rebuild trust in public transport, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…Prior to the emergence of the Omicron variant of SARS-CoV-2, numerous studies in various countries documented an association between a decline in population mobility and a subsequent reduction in reported case incidence [ 1 7 ]. The principal objective of the present study is to begin to assess whether this mobility-incidence relationship similarly prevailed during the more recent Omicron-driven wave.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the emergence of the Omicron variant of SARS-CoV-2, numerous studies in various countries documented an association between a decline in population mobility and a subsequent reduction in reported case incidence [ 1 7 ]. The principal objective of the present study is to begin to assess whether this mobility-incidence relationship similarly prevailed during the more recent Omicron-driven wave.…”
Section: Introductionmentioning
confidence: 99%
“…Similar positive but moderate correlation between COVID cases was also reported by Bhadra et al [ 45 ] across India. Meanwhile, Manzira et al [ 52 ] reported that population mobility can explain 36.2% of infection in Dublin City. According to Mu et al [ 53 ] higher population size and population density are among the factors that contribute to higher possibilities of contacts between people resulting in more risk of disease spread.…”
Section: Resultsmentioning
confidence: 99%
“…The suggests that shared bicycle networks are a more versatile means of transportation.#A region's transportation system plays a significant role in meeting the needs of mobility. Additionally, it plays an important role in the transmission and control of epidemics ( Manzira et al, 2022 ). Bike sharing systems can improve the transport system's resilience, or its capacity to continue moving people and products in the face of external disruption (Mattsson and Jenelius, 2015; Cheng et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%